Evaluation of the performance of some cultivars of Faba Bean Vicia faba L. under different levels of phosphorus - Algraishi, Ali Hussein Alwan; Alogaidi, Faez Fayad Mohammed (Journal of Kerbala for Agricultural Sciences, 2022)
A field experiment was carried out during winter season of 2021-2022 to study growth and yield performance of four faba bean cultivars (lo-cal, Spanish, Dutch and New Zealand) and evaluate their performance under three levels of phosphorus fertilizer (80, 120 and 160 kg ha-1). The experiment was applied in split plot design with three replications. results showed highly significant effects of fertilization on all measured traits, as the third level (160 kg ha-1) superior in all measured traits, and gave plant dry weight (171.33 g) and seed yield (4.403 Mg ha-1). local cultivar was superior in traits: plant height, total phosphorus content, phosphorus use efficiency and plant dry weight. As for New Zealand cultivar excelled in: number of branches, number of leaves, and phosphorus concentration in shoot. while Spanish cultivar was superior in total seed yield (5.295 Mg ha-1).